A Statistical analysis study on Amoxicillin capsules a product of La Croesus Pharma, Inc. - Buenviaje, Arlene C.; Concepcion, Tatiana Joy M.; Diaz, David John V. (Diliman, Quezon City College of Engineering, 2001)
La Croesus Pharma Inc. is a manufacturer of both branded and generic pharmaceuticals and household consumer products. One of their more popular products is the 500 milligrams Amoxicillin capsule. Like any production system, rejection of the finished products is a problem of the company. Thus, this study aims to decrease, if not totally eliminate, the rejection of Amoxicillin capsules. To achieve this, the study focused on the parameter with high rejection rate and with sufficient data as monitored and recorded by the company. In this particular case, the main problem is the high reject rate due to non-compliance to potency level specifications. Using the Ishikawa Diagram, the possible factors which affect the potency level of the capsules were determined and these are temperature and relative humidity. Exposing the Amoxicillin mixture to high temperatures cause the degradation of the active ingredients. Meanwhile, exposing it to high humidity causes the absorption of too much moisture which leads to the dilution of the active ingredients. The degradation and dilution of the active ingredients reduce the potency of the Amoxicillin capsules. Using Two-Factor Factorial Design, the effects of the factors and their interaction on percent potency were determined. From the analysis of variance, it was determined that only temperature has a significant effect on percent potency and from the results of the Duncan's Multiple Range Test, it was determined that temperatures of 22 and 23 degrees Celcius in particular have a significant effect on percent potency. However, these levels of temperature only account for around 17 percent of the variability of percent potency. Based on these findings from the statistical analysis, it was strongly recommended that the company establish better methods of controlling and monitoring temperature. Since there is low linear relationship between temperature and percent potency, it was also low linear relationship between temperature and percent potency, it was also recommended that the company perform a study on its production system in order to determine other factors that may be affecting the said parameter. Once these other factors have been determined, a better and more accurate statistical analysis study could be performed through the use of a p factorial design where k is the number of factors to be tested and p is the number of levels of the factors. Ultimately, these recommendations aim to increase the productivity and efficiency of the company's Amoxicillin production system.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics